"Life Isn't as Carefree as It Used to Be": A Mixed-Methods Evaluation of the Experiences of Women With Fear of Falling During Cancer Survivorship. Issue 1 (January 2021) - Covington, Kelley R.; Atler, Karen E.; Bailey, Jessica James A.; Lucas, Katie; Pergolotti, Mackenzi
Abstract : Purpose/Objective: To understand activities and experiences of women with fear of falling during cancer survivorship. Design: Parallel, mixed-methods design. Setting: Academic research. Participants and Measurement: Women who had completed active treatment and reported fear of falling completed structured surveys, the Timed Up and Go (TUG) test, a time-use assessment(s) guided by individual interview, and a focus group. Descriptive statistics, independent-samples t test, and exploratory Pearson correlations were used to analyze quantitative variables. Qualitative themes were identified through inductive, descriptive analysis. Results: Three (38%) participants had fallen in the past 6 months and 4 (50%) were considered at risk for falling (ie, TUG >10.7 seconds). Most of participants' time was spent at home versus away from home ( t = −1.2, P = .04) and in committed occupations ( M = 5.5 ± 2.1 hours; 34.8% of time per day). TUG fall risk (>10.7 seconds) and global mental health ( r = −0.83, P = .01), TUG time and Activities Balance Confidence ( r = −0.71, P < .05), and fear of falling and global mental health ( r = −0.76, P = .03) were significantly correlated. Fear of falling led to (1) identity challenges and (2) ongoing lifestyle adaptations during survivorship. Adaptations included increased awareness, avoidance, or making modifications to support (or diminish) participation in daily activities and roles while avoiding falls. Limitations: Small sample and lack of precancer data. Conclusions: Fear of falling is an important influence on women's activities and experiences during cancer survivorship. Fear of falling may negatively influence mental health and physical function. Women may experience identity challenges and the need to make ongoing adaptations to participate in important roles and activities during survivorship.